Penerapan manajemen risiko sebagai indikator penilaian kinerja di Lembaga X - Rochiyatun, Rochiyatun; Diyanty, Vera (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to formulate performance assessment indicators that have been integrated with the implementation of risk management in public sector organizations, namely Institution X. The background of this research was carried out because of the problems that arose from the results of the maturity baseline assessment of the implementation of the integrated government internal control system (SPIP) conducted by the Agency for Financial and Development Supervision (BPKP) in 2021, which stated that Echelon II leaders have not encouraged the application of risk management as an indicator of performance evaluation. The data used in this study were obtained from questionnaires and interviews, which were described using descriptive analysis techniques. The results of the study show that process risk or key risk indicators detected in risk assessment can be used as performance appraisal indicators that meet specific, measurable, achievable, relevant, and time-phased (SMART) criteria. The results of this study produce several performance assessment indicators that can be integrated with risk management, which can help public sector organizations improve performance and increase the value of SPIP maturity.